KONSEP KETUHANAN DALAM BRHADARANYAKA UPANISAD (Kajian Teologi Hindu) - I Putu Edi Sutrisna; Kadek Lestariani; Ni Luh Ayu Anugrah Wati (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2020)
In this article discusses the Concept of God in Bharadaranyaka Upanisad, where the concept of God in Upanisad is Monism and Nirguna Brahman. The concept of God who embraces Monism is explained in the Uparisad Bharadaranyaka that God resides or resides anywhere but nobody knows it and he is the one who believes in Monism. controlling the universe and its contents, He is the One in all things. Then the concept of Nirguna Brahman is Bharadaranyaka Upanisad explained that God is described without nature, without form, can not be thought but He is a thinker. God in such circumstances is difficult to express in words whatever words, He is Almighty so that not many people can reach Him (God).